A reassessment of the Japanese clinical diagnostic criteria of familial hypercholesterolemia in a hospital-based cohort using comprehensive genetic analysis - Hayato Tada; Hirofumi Okada; Akihiro Nomura; Atsushi Nohara; Soichiro Usui; Kenji Sakata; Masayuki Takamura; Masa-aki Kawashiri (Practical Laboratory Medicine, 2020)
Background: Clinical diagnostic criteria of familial hypercholesterolemia (FH) in Japan include LDL cholesterol ​≥ ​180 ​mg/dL, Achilles tendon thickness ​≥ ​9.0 ​mm, and family history. However, few data exist regarding its validation. Design and Methods: A series of 680 participants, with a mean LDL cholesterol of 175 ​mg/dL were enrolled at Kanazawa University Hospital between 2006 and 2018. All had full assessments of, LDL cholesterol, Achilles tendon X-rays, family history records, and genetic analysis of FH-associated genes (LDLR, APOB, and PCSK9). The area under the curve (AUC) of receiver operating characteristic (ROC) curve analysis predicting the presence of FH mutations by each clinical marker were assessed. Results: The optimal cutoff values predicting the presence of an FH-associated mutation were 181 ​mg/dL for LDL cholesterol and ≥7.0 ​mm for Achilles tendon thickness. AUCs predicting FH mutations were 0.827 for Achilles tendon thickness ≥9.0 ​mm, 0.889 for LDL cholesterol ≥180 ​mg/dL, and 0.906 for family history. If Achilles tendon thickness ≥7.0 ​mm was used as a clinical criterion, then 41 participants (6%) were newly diagnosed with FH and 86 (12%) were newly misclassified as FH. Conclusions: Current clinical diagnostic criteria of FH were validated in this cohort. We recommend considering a tentative diagnosis of “potential FH” if the Achilles tendon thickness is ​≥ ​7.0 ​mm and <9.0 ​mm rather than dismissing a diagnosis of FH.